2013
DOI: 10.3892/or.2013.2495
|View full text |Cite
|
Sign up to set email alerts
|

Caudatin induces cell apoptosis in gastric cancer cells through modulation of Wnt/β-catenin signaling

Abstract: Abstract. Caudatin has been reported to trigger apoptosis in several types of cancer cell lines. In the present study, we investigated whether caudatin has therapeutic value in gastric cancer and examined the effects of caudatin on the expression of β-catenin in human gastric carcinoma cell lines. Here, we showed that caudatin treatment resulted in a dose-and time-dependent inhibition of proliferation of the gastric carcinoma cell lines. Cell cycle analysis demonstrated that caudatin induced G0/G1 arrest and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…β-catenin which is the key molecule in this pathway, is a multifunctional protein (19), and acts as a key transcriptional factor in the Wnt pathway. It widely participates in the regulation of cell proliferation and migration (20,21). In the present study, we observed a significant effect of USP39 knockdown on β-catenin levels, consistent with reduced growth and migration.…”
Section: Discussionsupporting
confidence: 80%
“…β-catenin which is the key molecule in this pathway, is a multifunctional protein (19), and acts as a key transcriptional factor in the Wnt pathway. It widely participates in the regulation of cell proliferation and migration (20,21). In the present study, we observed a significant effect of USP39 knockdown on β-catenin levels, consistent with reduced growth and migration.…”
Section: Discussionsupporting
confidence: 80%
“…Caudatin, a C-21 steroidal glycoside, is mainly isolated from the traditional Chinese medicine 'baishouwu', which was the root tuber of Cynanchum auriculatum Royle ex Wight. It has been reported that the antitumor effect of caudatin has been shown to exhibit anti-proliferation effects against cancer cells of different origins, including glioblastoma, lung, gastric, and liver cancer (12)(13)(14)(15)(16). In our previous studies, caudatin induced apoptosis of AGS cells or the HGC-27 cell line (14).…”
Section: Introductionmentioning
confidence: 72%
“…It has been reported that the antitumor effect of caudatin has been shown to exhibit anti-proliferation effects against cancer cells of different origins, including glioblastoma, lung, gastric, and liver cancer (12)(13)(14)(15)(16). In our previous studies, caudatin induced apoptosis of AGS cells or the HGC-27 cell line (14). Wang et al found that caudatin had an inhibitory activity on the secretion of HBsAg and HBV DNA replication (17).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…1 ) is mainly isolated from the root of Cynanchum bungei Decne , a traditional Chinese medicine and health food, which has potent anti-hepatitis B virus (HBV) activity [3,4] . Moreover, many lines of evidence have shown that caudatin induced apoptosis of many cancer cells [5][6][7][8][9] .Currently, several analytical methods exist for quantifying caudatin in the plants and biological samples by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) [10][11][12] . Quantification and pharmacokinetics studies on constituents of Traditional Chinese Medicine in plasma are required to offer suitable references in clinical application.…”
mentioning
confidence: 99%